2022
DOI: 10.3389/fpls.2022.836269
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Lectin Receptor-Like Kinase 1 in Tomato Confers Resistance to Fusarium oxysporum f. sp. Radicis-Lycopersici

Abstract: The disease Fusarium crown and root rot (FCRR), caused mainly by Fusarium oxysporum f. sp. radicis-lycopersici (FORL), seriously affects commercial tomato [Solanum lycopersicum (Sl)] yields. However, the genes that offer resistance to FORL are limited and the mechanism of resistance to FCRR is poorly understood. Lectin receptor-like kinases (LecRKs) play critical roles in defensive responses and immunity in many plant species; however, whether specific LecRKs are involved in the response of tomato plants to FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 69 publications
(75 reference statements)
0
1
0
Order By: Relevance
“…Receptor-like kinases (RLKs) are well-known resistance genes (Goff and Ramonell 2007 ). RNA-seq data suggested that overexpression of lectin receptor-like kinases conferred resistance to Fusarium root rot in tomato (Yue et al 2022 ). Transcriptome data showed evidence for RLK-induced Fusarium wilt resistance in cotton and Arabidopsis by recognition of Fusarium through its cell wall extract (Babilonia et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Receptor-like kinases (RLKs) are well-known resistance genes (Goff and Ramonell 2007 ). RNA-seq data suggested that overexpression of lectin receptor-like kinases conferred resistance to Fusarium root rot in tomato (Yue et al 2022 ). Transcriptome data showed evidence for RLK-induced Fusarium wilt resistance in cotton and Arabidopsis by recognition of Fusarium through its cell wall extract (Babilonia et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%